Exploiting genomics for antimicrobial resistance surveillance at One Health interfaces - Muloi, Dishon; Jauneikaite, E.; Anjum, M.F.; Essack, S.Y.; Singleton, D.A.; Kasudi, M.R.; Wade, M.J.; Egyir, B.; Nunn, J.G.; Midega, J.T.; Peacock, S.J.; Feasey, N.A.; et al. (Elsevier, 2023)
The intersection of human, animal, and ecosystem health at One Health interfaces is recognised as being of key importance in the evolution and spread of antimicrobial resistance (AMR) and represents an important, and yet rarely realised opportunity to undertake vital AMR surveillance. A working group of international experts in pathogen genomics, AMR, and One Health convened to take part in a workshop series and online consultation focused on the opportunities and challenges facing genomic AMR surveillance in a range of settings. Here we outline the working group's discussion of the potential utility, advantages of, and barriers to, the implementation of genomic AMR surveillance at One Health interfaces and propose a series of recommendations for addressing these challenges. Embedding AMR surveillance at One Health interfaces will require the development of clear beneficial use cases, especially in low-income and middle-income countries. Evidence of directionality, risks to human and animal health, and potential trade implications were also identified by the working group as key issues. Addressing these challenges will be vital to enable genomic surveillance technology to reach its full potential for assessing the risk of transmission of AMR between the environment, animals, and humans at One Health interfaces.